2007
DOI: 10.1111/j.1863-2378.2007.01041.x
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Circovirus 2 Replication in Colostrum‐deprived Piglets Following Experimental Infection and Immune Stimulation Using A Modified Live Vaccine against Porcine Respiratory and Reproductive Syndrome Virus

Abstract: Porcine circovirus type 2 (PCV2) infection is now recognized as the major factor in the development of post-weaning multisystemic wasting syndrome (PMWS). Although Koch's postulates have been fulfilled for PCV2 and PMWS, the severe clinical expression of the disease observed in field cases has been difficult to reproduce experimentally. Some studies have demonstrated that immune stimulation associated with the use of some commercially available swine vaccines may trigger progression of PCV2 infection to diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Previous experimental studies documenting interactions between the PRRS MLV and PCV2 infection have yielded conflicting results. Allan et al (35) found that colostrum-deprived, specificpathogen-free (SPF) pigs infected with PCV2 at the age of 5 weeks and administered the PRRS MLV 1 week later had greater amounts of PCV2 antigen in tissues and more-severe histologic lesions, characteristic of PMWS, than pigs infected with PCV2 alone. However, the pigs failed to exhibit clinical signs or gross lesions typical of PCVAD (35).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous experimental studies documenting interactions between the PRRS MLV and PCV2 infection have yielded conflicting results. Allan et al (35) found that colostrum-deprived, specificpathogen-free (SPF) pigs infected with PCV2 at the age of 5 weeks and administered the PRRS MLV 1 week later had greater amounts of PCV2 antigen in tissues and more-severe histologic lesions, characteristic of PMWS, than pigs infected with PCV2 alone. However, the pigs failed to exhibit clinical signs or gross lesions typical of PCVAD (35).…”
Section: Discussionmentioning
confidence: 99%
“…Allan et al (35) found that colostrum-deprived, specificpathogen-free (SPF) pigs infected with PCV2 at the age of 5 weeks and administered the PRRS MLV 1 week later had greater amounts of PCV2 antigen in tissues and more-severe histologic lesions, characteristic of PMWS, than pigs infected with PCV2 alone. However, the pigs failed to exhibit clinical signs or gross lesions typical of PCVAD (35). In contrast, Opriessnig et al (36) evaluated the effects of PCV2 infection on the efficacy of the PRRS MLV in groups of 10 early-weaned SPF pigs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The early vaccination of piglets versus Mycoplasma hyopneumoniae was cited in certain trials (Allan et al., 2001; Kyriakis et al., 2002). Recently, using colostrum‐deprived piglets that were being vaccinated with a PRRS‐modified live vaccine and then infected with PCV2, the microscopical lesions and the PVC2‐antigen load associated to the lesions, were found to be higher in the vaccinated pigs (Allan et al., 2007b). But no clinical PMWS was obtained, and no typical macroscopic lesions, either.…”
Section: Pathogenesismentioning
confidence: 99%
“…Experimental infection of colostrum-deprived pigs demonstrated shedding of PCV2a DNA in feces, nasal, oropharyngeal and tonsillar secretions as early as one day post inoculation (dpi) [2, 6, 43]. Viremia, nasal, oropharyngeal, and fecal shedding of PCV2a DNA has been reported to persist at least 70 days in colostrum-deprived pigs [43].…”
Section: Introductionmentioning
confidence: 99%